ANALISIS KETERGANTUNGAN MAHASISWA TERHADAP PENGGUNAAN AI DALAM PROSES PEMBELAJARAN - Fajwah, Faizah; Septia Mayang Sari, Rukmana; Rahmadani, Fitra; Kamila, Zikra; Erja Dwi Putra, Gustiyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the extent to which students rely on artificial intelligence (AI) in the learning process and its impact on critical thinking skills. This study employs a descriptive qualitative approach through interviews and a literature review. The results indicate that AI offers various benefits in learning, such as improving learning efficiency, facilitating access to information, assisting with task completion, and fostering student creativity. However, excessive reliance on AI risks diminishing students’ ability to think independently, conduct in-depth analysis, and engage in critical reflection if they merely depend on instant answers without re-evaluating them. These findings also indicate that most students still use AI as a tool and reference while verifying the results provided. Therefore, the wise use of AI, combined with critical thinking skills, is necessary so that this technology can support the learning process without diminishing students’ independence and intellectual quality.